1991
DOI: 10.1172/jci115299
|View full text |Cite
|
Sign up to set email alerts
|

High levels of p19/nm23 protein in neuroblastoma are associated with advanced stage disease and with N-myc gene amplification.

Abstract: The gene encoding a novel protein designated nm23-H1, which was recently identified as identical to the A subunit of nucleotide diphosphate kinase from human erythrocytes, has been proposed to play a role in tumor metastasis suppression. We report that untreated neuroblastoma tumors contain a cellular polypeptide (M, = 19,000) designated p19, identified in two-dimensional electrophoretic gels, which occurs at significantly higher levels (P = 0.0001) in primary tumors containing amplified N-myc gene. The partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
1
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(140 citation statements)
references
References 11 publications
12
124
1
3
Order By: Relevance
“…Dans certains cas, il semblerait, paradoxalement, que leur absence inhibe la dissémination métastatique ou que leur pré-sence la favorise. Ainsi, NM23 est surexprimé dans les neuroblastomes les plus agressifs par rapport à ceux de stade précoce [35]. Une donnée récente rapporte que l'invalidation in vitro du gène MKK4 dans la lignée tumorale pancréatique PL5 inhibe la formation des métastases pulmonaires chez la souris nude [36].…”
Section: A Carcinome In Situunclassified
“…Dans certains cas, il semblerait, paradoxalement, que leur absence inhibe la dissémination métastatique ou que leur pré-sence la favorise. Ainsi, NM23 est surexprimé dans les neuroblastomes les plus agressifs par rapport à ceux de stade précoce [35]. Une donnée récente rapporte que l'invalidation in vitro du gène MKK4 dans la lignée tumorale pancréatique PL5 inhibe la formation des métastases pulmonaires chez la souris nude [36].…”
Section: A Carcinome In Situunclassified
“…Stathmin, also known as oncoprotein 18 or metablastin, is an evolutionarily conserved protein which is phosphorylated in response to growth and di erentiation factors (Dipaolo et al, 1996;Marklund et al, 1993), T-cell activation (Gratiot-Deans et al, 1992), embryonic development (Doye et al, 1992) and tissue regeneration (Koppel et al, 1993). Stathmin levels have been reported as elevated in acute leukemias/aggressive lymphomas (Roos et al, 1993), and neuroblastomas (Hallat et al, 1990). A recent report has identi®ed homology between TSG101 and a class of dominant-negative regulators of the ubiquitin conjugating enzyme E2, leading to the hypothesis that TSG101 may bind ubiquitin and inhibit cyclin degradation (Koonin and Abagyan, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been indicated an association of nm23 overexpression with a larger tumour in neuroblastoma, thyroid, gastric and renal cell carcinomas (Hailat et al, 1991;Zou et al, 1993;Park et al, 1995;Müller et al, 1998). Increasing evidences have suggested that nm23 be (Igawa et al, 1994;Caligo et al, 1995).…”
Section: Discussionmentioning
confidence: 89%
“…A few clinical results indeed indicated that nm23 expression, as anticipated from the in vitro investigations, correlated with better prognosis (Bevilacqua et al, 1989;Barnes et al, 1991;Hirayama et al, 1991;Nakayama et al, 1992;Campo et al, 1994;Hsu et al, 1999). Results from other studies, on the contrary, suggested that nm23 might facilitate tumour development and disease progression (Hailat et al, 1991;Zou et al, 1993;Müller et al, 1998;Pavelic et al, 2000). The discrepancy may be due to, in part, the difference of study design and, in part, study end point selected.…”
mentioning
confidence: 96%